2021
DOI: 10.3390/su132112113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Ingredients and Stabilisers on Properties of Mixes Based on Almond Drink for Vegan Ice Cream Production

Abstract: A plant-based diet is beneficial not only to human health but also for environmental sustainability. As consumers, we play a vital role in balancing hedonic consumption with long-term sustainable behaviours, such as reduced animal products consumption. As a result of the changeable trend in the food industry, there are considerably more requirements for food manufacturers. This study aimed to determine the influence of different ingredients and selected stabilisers (iota carrageenan and its acid and enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The partial coalescence of fat is responsible for stabilizing air cells and fat networks in the unfrozen matrix of ice cream mixes (Liu et al, 2022). In previous research by Kot et al (2021) and Kot, Kamińska‐Dwórznicka, and Jakubczyk (2022), vegan ice cream mixes with the same recipe such as those presented were prepared, and fat destabilization was confirmed. Coalescence, sedimentation, and creaming occurred during the maturation time of ice cream mixes.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The partial coalescence of fat is responsible for stabilizing air cells and fat networks in the unfrozen matrix of ice cream mixes (Liu et al, 2022). In previous research by Kot et al (2021) and Kot, Kamińska‐Dwórznicka, and Jakubczyk (2022), vegan ice cream mixes with the same recipe such as those presented were prepared, and fat destabilization was confirmed. Coalescence, sedimentation, and creaming occurred during the maturation time of ice cream mixes.…”
Section: Resultsmentioning
confidence: 73%
“…For other variants, this effect was not noticed, therefore it will not be possible to indicate the same tendency in all ice cream. In previous research by Kot et al (2021), it was observed that ultrasound homogenization increased the consistency index in ice cream mixes. According to Aslan and Dogan (2017), the shear forces which were generated by acoustic cavitation in emulsions were responsible for breaking oil droplets into small ones and allowed the better distribution of proteins on new interface systems.…”
Section: The Recrystallization Process In Ice Creammentioning
confidence: 88%
“…The microstructure of milk–vegetable ice cream is characterized by the presence of an additional framework of microbubbles, which wraps larger air inclusions and stabilizes them ( Figure 4 ). Other scientists [ 174 ] also looked at β-glucan’s ability to make foam, but this work [ 12 ] is the first to describe how this polysaccharide can make foam with a complex structure.…”
Section: The Use Of β-Glucan In the Technology Of Ice Cream And Froze...mentioning
confidence: 99%
“…Viscosity was increased from 15.81 to 36.40 cp with increasing quantity of WSPC and coconut fat. Peasura et al (2020) and Kot et al (2021) reported that increasing trend in viscosity might resulted from increasing carbohydrates which enhances the consistency of ice cream and prevents large air cells formation. Instrumental hardness of all samples varied significantly from lower to higher textural mean values.…”
Section: Physical and Rheological Quality Of Vegan Ice Creammentioning
confidence: 99%